AHP METHOD APPLICATION FOR LECTURER COMPETENCY ASSESSMENT: A STUDY CASE - Fauzi, Dede; Hanim, Hafizah; Ihksan, Muhammad; Susilo, Herman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
As a newly established higher education institution in Bukittinggi, Universitas Mohammad Natsir Bukittinggi (UMN Bukittinggi) is chosen as the study location since it required highly qualified and competent teaching staff to support its academic excellence. The competence of lecturers is a fundamental requirement that must be established by universities to enhance the quality of both the institution and its graduates. To determine the required competencies, the university has set specific criteria, including teaching quality, educational background, work ethic, and the quality of teaching materials. This research aims to build a desktop application with Analytic Hierarchy Process (AHP) in assessing lecture competency. Microsoft tools like Visual Studio and Visual Basic programming are used in the development of the application. The application maps the evaluation criteria of lecturer performance into a hierarchy, where each hierarchy will be a pairwise comparison between criteria so that a comparison of the relative importance between the criteria obtained. With the modeling utilizing Unified Modeling Language, this research also designs user interface modeling in the proposed application. Keywords: Lecturer Competence, Decision Support System, Analytical Hierarchy Process, Technological Competency